Disparities in the implementation of the Health Extension Program in Ethiopia: Doing more and better towards universal health coverage - Tilahun Nigatu Haregu; Yibeltal Kiflie Alemayehu; Yibeltal Assefa Alemu; Girmay Medhin; Mulu Abraha Woldegiorgis; Fasil Walelign Fentaye; Mulusew J. Gerbaba; Alula M. Teklu (Elsevier, 2022)
Introduction: Large-scale implementation of the Health Extension Program (HEP) has enabled Ethiopia to make significant progress in health services coverage and health outcomes. However, evidence on equity and disparities in the implementation of the HEP is limited. The aim of this study was to examine disparities in the implementation of the HEP in Ethiopia. Methods: We used data from the 2019 National HEP assessment which was conducted between Oct 2018 and Sept 2019 in nine regions in the country. Data were collected from 62 districts, 343 Health posts, 179 Health centres, 584 Health Extension Workers (HEWs), and 7043 women from 7122 Households. This study focused on selected input, service delivery, and coverage indicators. We used rate differences, rate ratios and index of disparity to assess disparities in HEP implementation across regions. Results: We found wide inter-regional disparities in HEP implementation. Developing regional states (DRS) had significantly lower availability of qualified HEWs (Rate Ratio (RR) = 0.54), proportion of households visited by Health Extension workers (RR = 0.40), and proportion of mothers who received education on child nutrition (RR = 0.45) as compared national average. There were also significant disparities in HEP implementation among DRS in the proportion of households visited by HEWs in the past 12 months (Index of disparity = 1.58) and proportion of adolescents who interacted with HEWs (Index of disparity = 1.43). Despite low overall coverage of health services in DRS, the contribution of the HEP for maternal health services was relatively high. Conclusion: There were significant inter-regional disparities in the implementation HEP in Ethiopia. The level of disparity among DRS was also remarkable. To achieve Universal Health Coverage, it is important that these disparities are addressed systematically and strategically. We recommend a tailored approach in HEP implementation in DRS.